As Defesas da Ilha de Santa Catarina e do Rio Grande de Sao Pedro em 1786 - Celis Estrada, Diego (2019)
This book is based on the original manuscript As Defesas da Ilha of Santa Catarina and Rio Grande de Sao Pedro, made up between 1786 and 1789 by the military engineer José Correia Rangel, a document that contains very valuable information: maps, tables, plants of the fortifications and uniforms of the troops of the time, as well as the history of Santa Catarina's and Rio Grande de San Pedro's fortifications. To this has been added some additional contents and others of didactic character (introductory texts and explanatory notes), which are complemented with photographs of the still existing fortifications, other illustrations of the time and a glossary.